Anti-reflection self-cleaning coating for photovoltaic module and preparation method of anti-reflection self-cleaning coating

By modifying SiO2 particles and multiple collaboratively designed coatings, the problems of surface pollution and light transmittance of photovoltaic modules are solved, self-cleaning and weather resistance are improved, and maintenance costs are reduced.

CN119752265AActive Publication Date: 2025-04-04DATANG CANGZHOU NEW ENERGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411800797.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-04
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

When photovoltaic modules are exposed outdoors, the surface of dust, oil and other impurities are easily adhered to, resulting in a decrease in light transmittance and accumulation of surface pollution. The existing cleaning methods increase maintenance costs and may damage the components.

Method used

Multiple collaborative designs of modified SiO2 particles, fluorine-containing compounds and silicone resins are adopted to improve light transmittance through optical regulation of nanostructures, low surface energy modification to achieve self-cleaning function, and a dense crosslinking network is formed to improve the weather resistance of the coating.

Benefits of technology

The self-cleaning function and light transmittance of the photovoltaic module surface are realized, while improving the weather resistance and chemical stability of the coating, reducing maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752265A_ABST
    Figure CN119752265A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of coatings, and provides an anti-reflection self-cleaning coating for a photovoltaic module and a preparation method of the anti-reflection self-cleaning coating. The preparation method comprises the following steps: synthesizing SiO2 particle sol by adopting a sol-gel method, carrying out condensation reaction on trifluoropropyltriethoxysilane and hydroxyl on the surfaces of SiO2 particles, and exposing trifluoropropyl on the surfaces of the SiO2 particles to reduce the surface energy; free radicals generated by decomposition of cyclopropyl ethyl trimethyl silyl acetal react with 1H, 1H-perfluorooctyl acrylate to form a long-chain perfluoropolymer, a perfluorooctyl side chain is introduced, and low surface energy and hydrophobicity are brought while the light transmittance is improved; methylated high imino melamine is used as a cross-linking agent, imino and methoxyl groups in the molecular structure of methylated high imino melamine react with carboxyl or hydroxyl to generate ether bonds so as to form a stable bonding structure, the cross-linking density is further improved, and the prepared coating can reduce light reflection on the surface of a photovoltaic module, improve the light transmittance and enhance the self-cleaning capacity of a coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings and relates to an anti-reflection self-cleaning coating for photovoltaic components and a preparation method thereof. Background Art

[0002] Photovoltaic power generation, as a sustainable and clean energy technology, has received widespread attention and application. Photovoltaic modules are exposed to the outdoors all year round, and dust, oil, leaves and other impurities are easily attached to the surface, especially in highly polluted environments such as deserts and industrial areas. This pollution will significantly reduce the light absorption capacity of the module. Existing cleaning methods such as manual cleaning or mechanical cleaning not only increase maintenance costs, but may also cause wear on the surface of the module. At the same time, traditional glass substrates or transparent packaging materials will lose part of the light energy due to surface reflection, resulting in insufficient light transmittance. In addition, surface optical inhomogeneity may further affect the transmission efficiency of light. Photovoltaic modules face two main problems in actual use: reduced light transmittance and accumulation of surface contamination. Therefore, the development of a coating with anti-reflection and self-cleaning functions has become an important direction to solve these problems. Summary of the invention

[0003] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an anti-reflection self-cleaning coating for photovoltaic modules and a preparation method thereof. The coating adopts a multiple coordinated design of modified SiO2 particles, fluorine-containing compounds and silicone resins, improves the transmittance through optical regulation of nanostructures, realizes the self-cleaning function through surface low surface energy modification, and forms a dense cross-linked network at the same time to improve the weather resistance of the coating, thereby meeting the needs of actual production.

[0004] To achieve this object, the present invention adopts the following technical solutions:

[0005] In a first aspect, the present invention provides a method for preparing an anti-reflection self-cleaning coating for a photovoltaic module, the preparation method comprising:

[0006] Step S1, dispersing polyacrylic acid in ammonia water to obtain a mixed solution, adding the mixed solution to anhydrous ethanol, and continuously stirring at a first stirring speed, then adding tetraethyl orthosilicate, and continuously stirring at a first stirring speed to form a SiO2 particle sol, heating the SiO2 particle sol to a first temperature and adding a trifluoropropyltriethoxysilane solution after adjusting the pH, and continuously reacting to obtain a modified SiO2 sol;

[0007] Step S2, uniformly dispersing cyclopropylethyltrimethylsilylacetal in 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, adding a reflux condenser and heating to a second temperature, and stirring at a second stirring speed to react to obtain a reaction solution A, dispersing benzoyl peroxide and 1H,1H-perfluorooctyl acrylate in another portion of 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether to obtain a reaction solution B, adding the reaction solution B to the reaction solution A, continuing the reaction at the second temperature, then heating to a third temperature and continuing the reaction, and cooling to room temperature after the reaction is completed to obtain a coating solution;

[0008] Step S3, under N2 atmosphere, methyl methacrylate, octyl acrylate, hydroxyethyl acrylate, 2-hydroxyethyl acrylic acid, bis-3-methacryloxypropylated tetramethyldisiloxane, azobisisobutyronitrile, and dodecanethiol are sequentially mixed, and then added into ethyl acetate at a fourth temperature for continuous reaction, and then heated to a fifth temperature for continuous reaction, and after the reaction is completed, cooled to room temperature to obtain a mixture, and then triethylamine is added to the mixture and stirred at a first stirring speed, and then deionized water is added, and stirred at a third stirring speed to obtain a coating precursor;

[0009] Step S4, dispersing the crosslinking agent in propylene glycol monomethyl ether acetate to form a crosslinking agent solution, mixing the modified SiO2 sol, the coating solution and the coating precursor, and then adding the crosslinking agent solution and continuously stirring at a second stirring speed to obtain an anti-reflective self-cleaning coating for photovoltaic modules.

[0010] The carboxyl groups in the polyacrylic acid molecules react with the ammonia molecules in the ammonia water to form carboxylates. The polyacrylic acid molecular chains are more easily dispersed in water due to electrostatic repulsion, forming a uniform polyacrylic acid solution and providing adsorption sites for the subsequent hydrolysis and condensation of tetraethyl orthosilicate. In the weakly alkaline environment provided by the ammonia water, the ethoxy groups of tetraethyl orthosilicate react with water to form silanol groups, which further form silicon-oxygen bonds through condensation reactions, and finally generate SiO2 particles. In this process, polyacrylic acid stabilizes SiO2 particles by electrostatic adsorption, preventing them from agglomerating while maintaining the uniformity of the particles. In the acidic condition of trifluoropropyltriethoxysilane solution, the ethoxy group reacts with water to form silanol groups. The silanol groups in the trifluoropropyltriethoxysilane solution undergo condensation reaction with the hydroxyl groups on the surface of SiO2 nanoparticles to form strong silicon-oxygen bonds. At the same time, the trifluoropropyl groups are exposed to the SiO2 surface, which reduces the surface energy and forms a hydrophobic coating, thereby realizing the self-cleaning function. The strong bonding through the silicon-oxygen bonds improves the weather resistance and chemical stability of the coating, and it can maintain its performance under long-term exposure to ultraviolet radiation and humid heat conditions in the photovoltaic environment.

[0011] The cyclopropyloxy group in cyclopropylethyltrimethylsilylacetal is a three-membered ring structure, a cyclic ether composed of two carbon atoms and one oxygen atom. There is a high tension in the ring, which makes its chemical bond less stable. Under thermal energy environment, one CO bond in the cyclopropyloxy group breaks, resulting in the ring opening. After the ring opening, the oxygen atom on the cyclopropyloxy group connects with the silicon atom of cyclopropylethyltrimethylsilylacetal to form a new siloxy group. The remaining carbon chain part forms an intermediate with an active group, providing a site for subsequent reactions; the OO bond of benzoyl peroxide is a weak bond and is easily thermally decomposed to generate two benzoyl radicals, which further decompose to generate phenyl radicals. The 1H,1H-perfluorooctyl acrylate molecule contains a carbon-carbon double bond. The double bond consists of a σ bond and a π bond, of which the π bond is weaker and easily attacked by nucleophilic or free radical species. When the phenyl radical contacts the double bond of the 1H,1H-perfluorooctyl acrylate molecule, the phenyl radical attacks the π electrons of the double bond, destroying the double bond, causing one of the carbon atoms to combine with the free radical, and the other carbon atom leaves an unpaired electron to form a new σ bond, while generating active chain free radicals. Due to the inductive effect of the perfluoro chain, the active chain free radical has a stable electron cloud distribution and is more likely to react with other molecules to form a long-chain perfluoroacrylate polymer. The perfluorooctyl side chain is introduced into the molecular structure, and the low refractive index of the perfluoro chain segment enables it to effectively reduce the loss of reflected light at the optical interface, improve light transmittance, and bring low surface energy and hydrophobic properties.

[0012] The carbon-carbon double bond of perfluorooctyl acrylate is the active center of the polymerization reaction. After free radical initiation, linear or branched chain segments are formed. During the chain growth process, a large number of side chains containing perfluoro groups are formed in the polymer. The high hydrophobicity and low polarity of these side chains provide hydrophobic properties for the coating. The perfluorooctyl acrylate chain during the polymerization process may form cross-links with cyclopropylethyltrimethylsilyl acetal to enhance the mechanical properties and chemical stability of the polymer. The cross-linking effect forms a three-dimensional network structure, which makes the coating have better wear resistance and adhesion.

[0013] Under nitrogen protection and the action of free radical initiator azobisisobutyronitrile, multiple monomers form copolymers through free radical polymerization, and the double bonds contained in the acrylate monomers form long-chain copolymers through free radical-initiated polymerization. Methyl methacrylate provides a hard skeleton to increase the hardness of the coating. Octyl acrylate introduces flexible segments to improve the toughness and adhesion of the coating and enhance weather resistance. Hydroxyethyl acrylate and 2-hydroxyethyl acrylic acid provide active hydroxyl sites for subsequent reactions with crosslinkers to form a three-dimensional network structure, improve the mechanical properties and chemical resistance of the coating, and bis-3-methylpropyleneoxypropylated tetramethyldisiloxane introduces silicon oxygen segments to improve hydrophobicity and weather resistance and enhance self-cleaning effects. This molecular design helps to balance the toughness and strength of the coating. During the polymerization process, dodecanethiol combines with free radicals through active hydrogen to regulate the molecular weight of the polymer, prevent excessive polymerization, and improve the stability of the coating. The core feature of methylated high-imino melamine as a cross-linking agent is that its molecular structure contains a large number of active imino and methoxy groups. The methoxy groups react with hydroxyl groups to generate ether bonds, forming a dense three-dimensional cross-linked network. The imino groups can react with carboxyl or hydroxyl groups to form a more stable bonding structure, further increasing the cross-linking density.

[0014] As a preferred technical solution of the present invention, in step S1,

[0015] The mass ratio of the polyacrylic acid, ammonia water, anhydrous ethanol and tetraethyl orthosilicate is (1-2): (10-15): (150-180): (2-3);

[0016] The mass fraction of the ammonia water is 15-20wt.%;

[0017] The stirring time after adding ethyl orthosilicate is 6-8h.

[0018] As a preferred technical solution of the present invention, in step S1,

[0019] The preparation method of the trifluoropropyl triethoxysilane solution is as follows: dissolving trifluoropropyl triethoxysilane in anhydrous ethanol to prepare a trifluoropropyl triethoxysilane solution, adding deionized water to the trifluoropropyl triethoxysilane solution and adjusting the pH, wherein the mass fraction of the trifluoropropyl triethoxysilane solution is 5-10wt.%; and the range of adjusting the pH is 4-5;

[0020] The first temperature is 40-50°C;

[0021] The mass ratio of the trifluoropropyltriethoxysilane solution and deionized water after the pH is adjusted is (10-15): (1-2);

[0022] The reaction time of adding the pH-adjusted trifluoropropyltriethoxysilane solution is 2-3 hours.

[0023] As a preferred technical solution of the present invention, in step S2,

[0024] The mass ratio of cyclopropylethyltrimethylsilyl acetal to 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether is (1-2):(70-80);

[0025] The mass ratio of the benzoyl peroxide, 1H,1H-perfluorooctyl acrylate and another portion of 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether is (0.5-1.0):(20-30):(40-50);

[0026] The second temperature is 65-75°C.

[0027] As a preferred technical solution of the present invention, in step S2,

[0028] The reaction time after the reaction solution B is added to the reaction solution A is 6-8h;

[0029] The third temperature is 80-90°C;

[0030] The reaction time at the third temperature is 2-3h.

[0031] As a preferred technical solution of the present invention, in step S3,

[0032] The mass ratio of the methyl methacrylate, octyl acrylate, hydroxyethyl acrylate, 2-hydroxyethyl acrylic acid, bis-3-methacryloxypropylated tetramethyldisiloxane, azobisisobutyronitrile, dodecanethiol, ethyl acetate, triethylamine and deionized water is (6-8): (6-8): (10-12): (1-3): (0.5-1): (0.2-0.5): (0.1-0.3): (40-50): (2-4): (20-30).

[0033] As a preferred technical solution of the present invention, in step S3,

[0034] The fourth temperature is 90-100° C.;

[0035] The reaction time at the fourth temperature is 1-2h.

[0036] As a preferred technical solution of the present invention, in step S3,

[0037] The fifth temperature is 100-110° C.;

[0038] The reaction time of the fifth temperature is 6-8h;

[0039] The stirring time after adding triethylamine is 30-50min.

[0040] As a preferred technical solution of the present invention, in step S4,

[0041] The cross-linking agent is methylated high-imino melamine;

[0042] The mass fraction of the cross-linking agent solution is 20-30wt.%;

[0043] The mass ratio of the modified SiO2 sol, the coating solution, the coating precursor solution, and the crosslinking agent solution is (30-50): (20-30): (30-50): (5-10);

[0044] The stirring time after adding the cross-linking agent is 20-30 minutes.

[0045] In a second aspect, the present invention provides an anti-reflective self-cleaning coating for a photovoltaic module prepared by the preparation method described in the first aspect.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] (1) Silica particles are prepared by a sol-gel process. The surface of SiO2 nanoparticles is fluorinated with trifluoropropyl triethoxysilane. The hydroxyl groups on the surface of the SiO2 nanoparticles undergo a condensation reaction to generate strong silicon-oxygen bonds. At the same time, the trifluoropropyl groups are exposed on the surface of SiO2, which reduces the surface energy and forms a hydrophobic coating, thereby achieving a self-cleaning function. The weather resistance and chemical stability of the coating are improved through the strong bonding of silicon-oxygen bonds, and the performance can be maintained in a long-term exposure environment;

[0048] (2) Cyclopropylethyltrimethylsilylacetal decomposes to generate phenyl radicals, which react with 1H,1H-perfluorooctyl acrylate to form a long-chain perfluoroacrylate polymer. Perfluorooctyl side chains are introduced into the molecular structure. The low refractive index of the perfluoro chain segment can effectively reduce the reflected light loss at the optical interface, improve the light transmittance, and bring low surface energy and hydrophobic properties;

[0049] (3) Multiple monomers form copolymers through free radical polymerization. The double bonds contained in acrylate monomers form long-chain copolymers through free radical-initiated polymerization. The core feature of methylated high-imino melamine as a cross-linking agent is that its molecular structure contains a large number of active imino and methoxy groups. The methoxy group reacts with the hydroxyl group to generate ether bonds, forming a dense three-dimensional cross-linked network. The imino group can react with the carboxyl group or the hydroxyl group to form a more stable bonding structure, further increasing the cross-linking density. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1A flow chart of a method for preparing an anti-reflective self-cleaning coating for a photovoltaic module provided in Examples 1-6 of the present invention;

[0051] Figure 2 This is a SEM image of the silicon dioxide particles prepared in Example 1 of the present invention;

[0052] Figure 3 : is the contact angle between the photovoltaic anti-reflective self-cleaning coating prepared in Example 1 of the present invention and water. DETAILED DESCRIPTION

[0053] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.

[0054] The chemical reagents used in the examples and comparative examples of the present invention are all commercially available products, and their brands, specifications and manufacturer information are as follows:

[0055] Polyacrylic acid, solid content ≥40%, Shandong Taihe Science and Technology Co., Ltd.;

[0056] Ammonia water, purity 25wt.%~28wt.%, Shandong Qingjia Chemical Co., Ltd.;

[0057] Anhydrous ethanol, purity ≥99%, Yonghua Chemical Co., Ltd.;

[0058] Tetraethyl orthosilicate, purity ≥98%, Shandong Sike New Materials Co., Ltd.;

[0059] Trifluoropropyltriethoxysilane, purity ≥98%, Quzhou Dongming Chemical Co., Ltd.;

[0060] Cyclopropylethyltrimethylsilyl acetal, purity ≥99%, Merck KGaA, Darmstadt, Germany;

[0061] 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, purity ≥98%, Shanghai Aladdin Biochemical Technology Co., Ltd. Benzoyl peroxide, purity ≥99%, Taizhou Zhongteng Chemical Materials Co., Ltd.;

[0062] 1H,1H-Perfluorooctyl acrylate, purity ≥95%, Changzhou New Fluoro Chemical Co., Ltd.;

[0063] Methyl methacrylate, purity ≥98%, Shandong Hefeng Chemical Co., Ltd.;

[0064] Octyl acrylate, purity ≥98%, Shandong Derui Polymer Materials Co., Ltd.;

[0065] Hydroxyethyl acrylate, purity ≥98%, Shandong Derui Polymer Materials Co., Ltd.;

[0066] 2-Hydroxyethyl acrylic acid, purity ≥99%, Guangzhou Sanwang Chemical Materials Co., Ltd.;

[0067] Bis-3-methacryloxypropylated tetramethyldisiloxane, purity ≥95%, Aike Fine Chemicals Co., Ltd.

[0068] Azobisisobutyronitrile, purity ≥99%, Jinan Century Tongda Chemical Co., Ltd.;

[0069] Dodecanethiol, purity ≥99%, Jinan Century Tongda Chemical Co., Ltd.;

[0070] Ethyl acetate, purity ≥99%, Shandong Xuanhai Chemical Co., Ltd.;

[0071] Triethylamine, purity ≥99%, Shandong Liding Chemical Technology Co., Ltd.

[0072] Methylated high-imino melamine, purity ≥99%, Shanghai Kaiyin Chemical Co., Ltd.;

[0073] Propylene glycol monomethyl ether acetate, purity ≥99%, Jiangsu Dena Chemical Co., Ltd.;

[0074] Other raw materials can be purchased from the market.

[0075] Example 1

[0076] This embodiment provides a method for preparing an anti-reflection self-cleaning coating for a photovoltaic module. Figure 1 As shown, the preparation method specifically comprises the following steps:

[0077] Step S1, dispersing 1.2g of polyacrylic acid in 12g of 16wt.% ammonia water to obtain a mixed solution, adding the mixed solution to 155g of anhydrous ethanol, and stirring at 310rpm for 32min, then adding 2.2g of tetraethyl orthosilicate, and stirring at 310rpm for 6.3h to form a SiO2 particle sol, dissolving trifluoropropyl triethoxysilane in anhydrous ethanol to prepare a 5.6wt.% trifluoropropyl triethoxysilane solution, adding 1.3g of deionized water to the trifluoropropyl triethoxysilane solution and adjusting the pH to 4.2, heating the SiO2 particle sol to 42°C and adding 13g of the pH-adjusted trifluoropropyl triethoxysilane solution, and continuing the reaction for 2.1h to obtain a modified SiO2 sol;

[0078] Step S2, 1.6 g of cyclopropylethyltrimethylsilylacetal is uniformly dispersed in 73 g of 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, and the temperature is raised to 67° C. after adding a reflux condenser, and the mixture is stirred at 220 rpm for reaction for 2.1 h to obtain a reaction solution A, 0.58 g of benzoyl peroxide and 23 g of 1H,1H-perfluorooctyl acrylate are dispersed in 46 g of 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether to obtain a reaction solution B, and the reaction solution B is added to the reaction solution A, and the reaction is continued at 67° C. for 6.5 h, and then the temperature is raised to 82° C. for continuous reaction for 2.3 h. After the reaction is completed, the mixture is cooled to room temperature to obtain a coating solution;

[0079] Step S3, under N2 atmosphere, 6.3g of methyl methacrylate, 6.4g of octyl acrylate, 10.8g of hydroxyethyl acrylate, 1.6g of 2-hydroxyethyl acrylic acid, 0.59g of bis-3-methacryloxypropylated tetramethyldisiloxane, 0.26g of azobisisobutyronitrile, and 0.14g of dodecanethiol were mixed in sequence, added to 44g of ethyl acetate at 92°C and reacted for 1.2h, then heated to 103°C and continued to react for 6.3h, cooled to room temperature after the reaction to obtain a mixture, then added 2.1g of triethylamine to the mixture and stirred at 320rpm for 36min, then added 23g of deionized water, and stirred at 880rpm for 24min to obtain a coating precursor;

[0080] Step S4, dispersing methylated high-imino melamine in propylene glycol monomethyl ether acetate to form a 26wt.% methylated high-imino melamine solution, mixing 36g of modified SiO2 sol, 24g of coating solution and 38g of coating precursor, and then adding 5.8g of cross-linking agent methylated high-imino melamine solution and stirring continuously at 230rpm for 26min to obtain an anti-reflection self-cleaning coating for photovoltaic modules.

[0081] Figure 2This is a SEM image of the silicon dioxide particles prepared in this example; Figure 3 This is the contact angle between the photovoltaic anti-reflective self-cleaning coating prepared in this example and water. The contact angle is 145°, indicating that the coating has obvious hydrophobicity.

[0082] Example 2

[0083] This embodiment provides a method for preparing an anti-reflection self-cleaning coating for a photovoltaic module. Figure 1 As shown, the preparation method specifically comprises the following steps:

[0084] Step S1, dispersing 1.5g of polyacrylic acid in 13g of 18wt.% ammonia water to obtain a mixed solution, adding the mixed solution to 159g of anhydrous ethanol, and stirring at 340rpm for 36min, then adding 2.5g of tetraethyl orthosilicate, and stirring at 340rpm for 6.6h to form a SiO2 particle sol, dissolving trifluoropropyl triethoxysilane in anhydrous ethanol to prepare a 5.9wt.% trifluoropropyl triethoxysilane solution, adding 1.4g of deionized water to the trifluoropropyl triethoxysilane solution and adjusting the pH to 4.6, heating the SiO2 particle sol to 44°C and adding 12g of the pH-adjusted trifluoropropyl triethoxysilane solution, and continuing the reaction for 2.3h to obtain a modified SiO2 sol;

[0085] Step S2, 1.2 g of cyclopropylethyltrimethylsilylacetal is uniformly dispersed in 74 g of 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, and the temperature is raised to 69° C. after adding a reflux condenser, and the mixture is stirred at 240 rpm for reaction for 2.3 h to obtain a reaction solution A, 0.63 g of benzoyl peroxide and 22 g of 1H,1H-perfluorooctyl acrylate are dispersed in 42 g of 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether to obtain a reaction solution B, and the reaction solution B is added to the reaction solution A, and the reaction is continued at 69° C. for 6.9 h, and then the temperature is raised to 85° C. for continuous reaction for 2.5 h. After the reaction is completed, the mixture is cooled to room temperature to obtain a coating solution;

[0086] Step S3, under N2 atmosphere, 6.4g methyl methacrylate, 6.1g octyl acrylate, 10.5g hydroxyethyl acrylate, 1.2g 2-hydroxyethyl acrylic acid, 0.63g bis-3-methacryloxypropylated tetramethyldisiloxane, 0.33g azobisisobutyronitrile, and 0.18g dodecanethiol were mixed in sequence, added to 42g ethyl acetate at 95°C for continuous reaction for 1.5h, then heated to 107°C for continuous reaction for 7.2h, cooled to room temperature after the reaction to obtain a mixture, then 2.5g triethylamine was added to the mixture, stirred at 350rpm for 32min, then 24g deionized water was added, and stirred at 900rpm for 28min to obtain a coating precursor;

[0087] Step S4, dispersing methylated high-imino melamine in propylene glycol monomethyl ether acetate to form a 22wt.% methylated high-imino melamine solution, mixing 33g of modified SiO2 sol, 26g of coating solution and 33g of coating precursor, and then adding 6.1g of cross-linking agent methylated high-imino melamine solution and stirring continuously at 250rpm for 24min to obtain an anti-reflection self-cleaning coating for photovoltaic modules.

[0088] Example 3

[0089] This embodiment provides a method for preparing an anti-reflection self-cleaning coating for a photovoltaic module. Figure 1 As shown, the preparation method specifically comprises the following steps:

[0090] Step S1, dispersing 1.1g of polyacrylic acid in 11g of 15.5wt.% ammonia water to obtain a mixed solution, adding the mixed solution to 163g of anhydrous ethanol, and stirring at 330rpm for 37min, then adding 2.1g of tetraethyl orthosilicate, and stirring at 330rpm for 7.1h to form a SiO2 particle sol, dissolving trifluoropropyl triethoxysilane in anhydrous ethanol to prepare a 6.4wt.% trifluoropropyl triethoxysilane solution, adding 1.1g of deionized water to the trifluoropropyl triethoxysilane solution and adjusting the pH to 4.4, heating the SiO2 particle sol to 41°C and adding 10g of the pH-adjusted trifluoropropyl triethoxysilane solution, and continuing the reaction for 2.0h to obtain a modified SiO2 sol;

[0091] Step S2, 1.3 g of cyclopropylethyltrimethylsilylacetal is uniformly dispersed in 71 g of 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, and the temperature is raised to 70° C. after adding a reflux condenser, and the mixture is stirred at 270 rpm for reaction for 2.6 h to obtain a reaction solution A, 0.68 g of benzoyl peroxide and 25 g of 1H,1H-perfluorooctyl acrylate are dispersed in 46 g of 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether to obtain a reaction solution B, and the reaction solution B is added to the reaction solution A, and the reaction is continued at 70° C. for 6.4 h, and then the temperature is raised to 83° C. for continuous reaction for 2.2 h. After the reaction is completed, the mixture is cooled to room temperature to obtain a coating solution;

[0092] Step S3, under N2 atmosphere, 7.1g methyl methacrylate, 7.3g octyl acrylate, 11.3g hydroxyethyl acrylate, 1.9g 2-hydroxyethyl acrylic acid, 0.68g bis-3-methacryloxypropylated tetramethyldisiloxane, 0.37g azobisisobutyronitrile, and 0.22g dodecanethiol were mixed in sequence, added to 44g ethyl acetate at 96°C and reacted for 1.6h, then heated to 105°C and continued to react for 6.7h, cooled to room temperature after the reaction to obtain a mixture, then added 2.8g triethylamine to the mixture and stirred at 360rpm for 37min, then added 20g deionized water, and stirred at 930rpm for 23min to obtain a coating precursor;

[0093] Step S4, dispersing methylated high-imino melamine in propylene glycol monomethyl ether acetate to form a 26wt.% methylated high-imino melamine solution, mixing 41g of modified SiO2 sol, 23g of coating solution and 39g of coating precursor, and then adding 6.4g of cross-linking agent methylated high-imino melamine solution and stirring continuously at 230rpm for 22min to obtain an anti-reflection self-cleaning coating for photovoltaic modules.

[0094] Example 4

[0095] This embodiment provides a method for preparing an anti-reflection self-cleaning coating for a photovoltaic module. Figure 1 As shown, the preparation method specifically comprises the following steps:

[0096] Step S1, dispersing 1.7g of polyacrylic acid in 14g of 17.5wt.% ammonia water to obtain a mixed solution, adding the mixed solution to 169g of anhydrous ethanol, and stirring at 380rpm for 42min, then adding 2.3g of tetraethyl orthosilicate, and stirring at 380rpm for 7.2h to form a SiO2 particle sol, dissolving trifluoropropyl triethoxysilane in anhydrous ethanol to prepare a 7.6wt.% trifluoropropyl triethoxysilane solution, adding 1.6g of deionized water to the trifluoropropyl triethoxysilane solution and adjusting the pH to 4.7, heating the SiO2 particle sol to 46°C and adding 13.5g of the pH-adjusted trifluoropropyl triethoxysilane solution, and continuing the reaction for 2.6h to obtain a modified SiO2 sol;

[0097] Step S2, 1.6 g of cyclopropylethyltrimethylsilylacetal is uniformly dispersed in 74 g of 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, and the temperature is raised to 73° C. after adding a reflux condenser, and the mixture is stirred at 220 rpm for reaction for 2.4 h to obtain a reaction solution A, 0.77 g of benzoyl peroxide and 26 g of 1H,1H-perfluorooctyl acrylate are dispersed in 43 g of 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether to obtain a reaction solution B, and the reaction solution B is added to the reaction solution A, and the reaction is continued at 73° C. for 7.1 h, and then the temperature is raised to 81° C. for continuous reaction for 2.4 h, and after the reaction is completed, the mixture is cooled to room temperature to obtain a coating solution;

[0098] Step S3, under N2 atmosphere, 6.6g of methyl methacrylate, 7.0g of octyl acrylate, 10.8g of hydroxyethyl acrylate, 2.3g of 2-hydroxyethyl acrylic acid, 0.76g of bis-3-methacryloxypropylated tetramethyldisiloxane, 0.41g of azobisisobutyronitrile, and 0.20g of dodecanethiol were mixed in sequence, added to 41g of ethyl acetate at 92°C and reacted for 1.3h, then heated to 102°C and continued to react for 7.2h, cooled to room temperature after the reaction to obtain a mixture, then added 3.2g of triethylamine to the mixture and stirred at 320rpm for 42min, then added 23g of deionized water, and stirred at 950rpm for 22min to obtain a coating precursor;

[0099] Step S4, dispersing methylated high-imino melamine in propylene glycol monomethyl ether acetate to form a 21wt.% methylated high-imino melamine solution, mixing 43g of modified SiO2 sol, 25g of coating solution and 45g of coating precursor, and then adding 7.6g of cross-linking agent methylated high-imino melamine solution and stirring continuously at 260rpm for 25min to obtain an anti-reflection self-cleaning coating for photovoltaic modules.

[0100] Example 5

[0101] This embodiment provides a method for preparing an anti-reflection self-cleaning coating for a photovoltaic module. Figure 1 As shown, the preparation method specifically comprises the following steps:

[0102] Step S1, dispersing 1.8g of polyacrylic acid in 15g of 16wt.% ammonia water to obtain a mixed solution, adding the mixed solution to 173g of anhydrous ethanol, and stirring at 340rpm for 44min, then adding 2.6g of tetraethyl orthosilicate, and stirring at 340rpm for 7.4h to form a SiO2 particle sol, dissolving trifluoropropyl triethoxysilane in anhydrous ethanol to prepare a 7.9wt.% trifluoropropyl triethoxysilane solution, adding 1.5g of deionized water to the trifluoropropyl triethoxysilane solution and adjusting the pH to 4.3, heating the SiO2 particle sol to 42°C and adding 12.7g of the pH-adjusted trifluoropropyl triethoxysilane solution, and continuing the reaction for 2.4h to obtain a modified SiO2 sol;

[0103] Step S2, 1.8 g of cyclopropylethyltrimethylsilylacetal is uniformly dispersed in 78 g of 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, and the temperature is raised to 75° C. after adding a reflux condenser, and the mixture is stirred at 260 rpm for reaction for 2.7 h to obtain a reaction solution A, 0.84 g of benzoyl peroxide and 23 g of 1H,1H-perfluorooctyl acrylate are dispersed in 47 g of 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether to obtain a reaction solution B, and the reaction solution B is added to the reaction solution A, and the reaction is continued at 75° C. for 7.6 h, and then the temperature is raised to 86° C. for continuous reaction for 2.8 h. After the reaction is completed, the mixture is cooled to room temperature to obtain a coating solution;

[0104] Step S3, under N2 atmosphere, 7.4g of methyl methacrylate, 7.8g of octyl acrylate, 11.5g of hydroxyethyl acrylate, 2.6g of 2-hydroxyethyl acrylic acid, 0.79g of bis-3-methacryloxypropylated tetramethyldisiloxane, 0.43g of azobisisobutyronitrile, and 0.23g of dodecanethiol were mixed in sequence, added to 44g of ethyl acetate at 95°C and reacted for 1.7h, then heated to 107°C and continued to react for 7.1h, cooled to room temperature after the reaction to obtain a mixture, then added 2.7g of triethylamine to the mixture, stirred at 340rpm for 40min, then added 24g of deionized water, and stirred at 1000rpm for 24min to obtain a coating precursor;

[0105] Step S4, dispersing methylated high-imino melamine in propylene glycol monomethyl ether acetate to form a 24wt.% methylated high-imino melamine solution, mixing 46g of modified SiO2 sol, 23g of coating solution and 42g of coating precursor, and then adding 8.4g of cross-linking agent methylated high-imino melamine solution and stirring continuously at 220rpm for 28min to obtain an anti-reflection self-cleaning coating for photovoltaic modules.

[0106] Example 6

[0107] This embodiment provides a method for preparing an anti-reflection self-cleaning coating for a photovoltaic module. Figure 1 As shown, the preparation method specifically comprises the following steps:

[0108] Step S1, dispersing 1.3g of polyacrylic acid in 12g of 17wt.% ammonia water to obtain a mixed solution, adding the mixed solution to 162g of anhydrous ethanol, and stirring at 350rpm for 40min, then adding 2.2g of tetraethyl orthosilicate, and stirring at 350rpm for 7.0h to form a SiO2 particle sol, dissolving trifluoropropyl triethoxysilane in anhydrous ethanol to prepare an 8.2wt.% trifluoropropyl triethoxysilane solution, adding 1.7g of deionized water to the trifluoropropyl triethoxysilane solution and adjusting the pH to 4.8, heating the SiO2 particle sol to 46°C and adding 13.6g of the pH-adjusted trifluoropropyl triethoxysilane solution, and continuing the reaction for 2.7h to obtain a modified SiO2 sol;

[0109] Step S2, 1.5 g of cyclopropylethyltrimethylsilylacetal is uniformly dispersed in 73 g of 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, and the temperature is raised to 72° C. after adding a reflux condenser, and the mixture is stirred at 240 rpm for reaction for 2.3 h to obtain a reaction solution A, 0.81 g of benzoyl peroxide and 26 g of 1H,1H-perfluorooctyl acrylate are dispersed in 42 g of 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether to obtain a reaction solution B, and the reaction solution B is added to the reaction solution A, and the reaction is continued at 72° C. for 7.6 h, and then the temperature is raised to 88° C. for continuous reaction for 2.5 h. After the reaction is completed, the mixture is cooled to room temperature to obtain a coating solution;

[0110] Step S3, under N2 atmosphere, 7.3g of methyl methacrylate, 7.1g of octyl acrylate, 10.7g of hydroxyethyl acrylate, 2.2g of 2-hydroxyethyl acrylic acid, 0.86g of bis-3-methacryloxypropylated tetramethyldisiloxane, 0.41g of azobisisobutyronitrile, and 0.26g of dodecanethiol were mixed in sequence, added to 47g of ethyl acetate at 97°C and reacted for 1.5h, then heated to 109°C and continued to react for 7.3h, cooled to room temperature after the reaction to obtain a mixture, then added 2.4g of triethylamine to the mixture and stirred at 360rpm for 43min, then added 27g of deionized water, and stirred at 930rpm for 27min to obtain a coating precursor;

[0111] Step S4, dispersing methylated high-imino melamine in propylene glycol monomethyl ether acetate to form a 28wt.% methylated high-imino melamine solution, mixing 41g of modified SiO2 sol, 25g of coating solution and 39g of coating precursor, and then adding 8.9g of cross-linking agent methylated high-imino melamine solution and stirring continuously at 260rpm for 24min to obtain an anti-reflection self-cleaning coating for photovoltaic modules.

[0112] Comparative Example 1

[0113] This comparative example provides a method for preparing an anti-reflection self-cleaning coating for a photovoltaic module. The difference from Example 1 is that the mass of the trifluoropropyl triethoxysilane solution after the pH is adjusted in step S1 is adjusted to 18 g, which is 5 g more than that in Example 1. The increased mass is deducted from polyacrylic acid, ammonia water, anhydrous ethanol and tetraethyl orthosilicate in equal proportions, so that the mass ratio between the components other than the trifluoropropyl triethoxysilane solution after the pH is adjusted remains unchanged, and the other process parameters and operating conditions are exactly the same as those in Example 1.

[0114] Comparative Example 2

[0115] This comparative example provides a method for preparing an anti-reflection self-cleaning coating for a photovoltaic module. The difference from Example 1 is that the mass of the trifluoropropyltriethoxysilane solution after the pH is adjusted in step S1 is adjusted to 8 g, which is 5 g less than that in Example 1. The reduced mass is added to polyacrylic acid, ammonia water, anhydrous ethanol and tetraethyl orthosilicate in equal proportion, so that the mass ratio of the components other than the trifluoropropyltriethoxysilane solution after the pH is adjusted remains unchanged, and the other process parameters and operating conditions are exactly the same as those in Example 1.

[0116] Comparative Example 3

[0117] This comparative example provides a method for preparing an anti-reflection self-cleaning coating for a photovoltaic module. The difference from Example 1 is that the mass of cyclopropylethyltrimethylsilylacetal in step S2 is adjusted to 2.4 g, which is 0.8 g more than that in Example 1. The increased mass is deducted from 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, benzoyl peroxide and 1H,1H-perfluorooctyl acrylate in equal proportions, so that the mass ratio between the components except cyclopropylethyltrimethylsilylacetal remains unchanged, and the other process parameters and operating conditions are exactly the same as those in Example 1.

[0118] Comparative Example 4

[0119] This comparative example provides a method for preparing an anti-reflection self-cleaning coating for a photovoltaic module. The difference from Example 1 is that the mass of cyclopropylethyltrimethylsilylacetal in step S2 is adjusted to 0.8 g, which is 0.8 g less than that in Example 1, and the reduced mass is proportionally added to 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, benzoyl peroxide and 1H,1H-perfluorooctyl acrylate, so that the mass ratio between the components except cyclopropylethyltrimethylsilylacetal remains unchanged, and the other process parameters and operating conditions are exactly the same as those in Example 1.

[0120] The test standard for light transmittance of the coating in the present invention is GB / T 2410-2008; the test standard for stain resistance is GB / T9780-2013; the test standard for weather resistance is GB / T 14522-2008; the test standard for adhesion is GB / T 9286-2021; the test samples are and the test results are shown in Table 1.

[0121] Table 1 Test results of anti-reflection self-cleaning coating for photovoltaic modules in Examples 1-6 and Comparative Examples 1-4

[0122] Light transmittance (%) Stain resistance Weather resistance / 300h Adhesion Example 1 93 Level 0 No bubbles, no cracks Level 0 Example 2 94 Level 0 No bubbles, no cracks Level 0 Example 3 92 Level 0 No bubbles, no cracks Level 0 Example 4 93 Level 0 No bubbles, no cracks Level 0 Example 5 91 Level 0 No bubbles, no cracks Level 0 Example 6 94 Level 0 No bubbles, no cracks Level 0 Comparative Example 1 86 Level 1 Slight cracking Level 1 Comparative Example 2 84 Level 1 Slight cracking Level 2 Comparative Example 3 83 Level 1 There are bubbles Level 2 Comparative Example 4 84 Level 2 Slight cracking Level 1

[0123] It can be seen from the data in Table 1 that the transmittance, stain resistance, weather resistance and adhesion of Comparative Example 1 are all lower than those of Example 1; the transmittance, stain resistance, weather resistance and adhesion of Comparative Example 2 are all lower than those of Example 1. This is because the mass of the trifluoropropyl triethoxysilane solution after pH adjustment in Comparative Example 1 is excessive, and it does not completely react with the surface of SiO2 particles, and remains in the coating to form small molecular impurities or oligomers. These products are difficult to form a stable structure after curing, thereby affecting the adhesion of the coating; excessive trifluoropropyl chain groups accumulate on the surface of SiO2 particles, resulting in the formation of irregular microscopic rough structures between particles, reducing the transmittance of the coating; excessive unreacted trifluoropropyl triethoxysilane may undergo photochemical degradation under the action of ultraviolet light, releasing small molecular substances, thereby destroying the chemical stability of the coating and reducing weather resistance; excessive use of trifluoropropyl triethoxysilane may cause areas with uneven molecular arrangement on the surface, the surface energy of these areas is relatively high, the local hydrophobicity is weakened, and the overall stain resistance of the coating is reduced. In Comparative Example 2, the quality of the trifluoropropyltriethoxysilane solution after pH adjustment is insufficient. When the surface of the SiO2 particles is insufficiently modified, fewer chemical bonds are formed between the SiO2 particles and the substrate, resulting in reduced interfacial adhesion and poor adhesion. The residual hydroxyl groups on the surface of the SiO2 particles will increase the polarity unevenness of the coating, causing light scattering and reducing the light transmittance of the coating. The exposed surface of the SiO2 particles is more likely to react with water and oxygen in the environment, and the coating may deteriorate or crack in the long term, and its weather resistance will decrease. The surface of the incompletely modified SiO2 particles has higher surface energy and stronger hydrophilicity, and is easily adsorbed with dirt and moisture, resulting in decreased stain resistance.

[0124] The light transmittance, stain resistance, weather resistance and adhesion of Comparative Example 3 are all lower than those of Example 1; the light transmittance, stain resistance, weather resistance and adhesion of Comparative Example 4 are all lower than those of Example 1. This is because in Comparative Example 3, there is an excess of cyclopropyl ethyl trimethylsilyl acetal, and the excess cyclopropyl ethyl acetal does not completely participate in the cross-linking during the reaction, and a large amount of unreacted small molecules or oligomers may remain, which may cause phase separation in the coating, weaken the chemical bonding force between the coating and the substrate, and reduce the adhesion; an excess of cyclopropyl ethyl acetal may cause residual oligosiloxane after the reaction, increase the unevenness of the coating, and may scatter light and reduce the light transmittance; unreacted cyclopropyl ethyl acetal may degrade under the action of ultraviolet light to generate volatile organic compounds, which accelerates the aging of the coating; an excessive amount of cyclopropyl ethyl acetal forms an irregular branched structure, which may affect the uniformity of the surface, make the coating surface partially hydrophilic, and reduce the stain resistance. In Comparative Example 4, cyclopropyl ethyl trimethyl silyl acetal is insufficient, the cross-linking network is insufficient, the number of siloxane bonds is small, the chemical bonding between the coating and the substrate is weakened, and the adhesion is reduced; when cyclopropyl ethyl trimethyl silyl acetal is insufficient, the network density is insufficient, micropores or defects may be formed inside the coating, and light is scattered; the cross-linking network is incomplete, lacking a complete protective barrier, ultraviolet light may penetrate and destroy the coating structure, resulting in reduced weather resistance; the cyclopropyloxy group in the cyclopropyl ethyl acetal is broken to generate reactive siloxane alcohol groups, the cyclopropyl ethyl acetal is insufficient, the bonding with fluoride is reduced, the surface energy cannot be significantly reduced, and the stain resistance is reduced.

[0125] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing an anti-reflection self-cleaning coating for photovoltaic modules, characterized in that: The preparation method is: Step S1, dispersing polyacrylic acid in ammonia water to obtain a mixed solution, adding the mixed solution into anhydrous ethanol and continuously stirring, then adding tetraethyl orthosilicate and continuously stirring to form a SiO2 particle sol, heating the SiO2 particle sol to a first temperature and adding a trifluoropropyltriethoxysilane solution after adjusting the pH, and continuously reacting to obtain a modified SiO2 sol; Step S2, uniformly dispersing cyclopropylethyltrimethylsilylacetal in 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, adding a reflux condenser, heating to a second temperature and stirring for reaction to obtain a reaction solution A, dispersing benzoyl peroxide and 1H,1H-perfluorooctyl acrylate in another portion of 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether to obtain a reaction solution B, adding the reaction solution B to the reaction solution A, continuing the reaction at the second temperature, then heating to a third temperature for continuous reaction, and cooling to room temperature after the reaction is completed to obtain a coating solution; Step S3, under N2 atmosphere, methyl methacrylate, octyl acrylate, hydroxyethyl acrylate, 2-hydroxyethyl acrylic acid, bis-3-methacryloxypropylated tetramethyldisiloxane, azobisisobutyronitrile, and dodecanethiol are sequentially mixed, added into ethyl acetate at a fourth temperature for continuous reaction, then heated to a fifth temperature for continuous reaction, cooled to room temperature after the reaction is completed to obtain a mixture, triethylamine is added into the mixture and stirred, deionized water is added, and continuous stirring is performed to obtain a coating precursor; Step S4, dispersing the crosslinking agent in propylene glycol monomethyl ether acetate to form a crosslinking agent solution, mixing the modified SiO2 sol, the coating solution and the coating precursor, and then adding the crosslinking agent solution and continuously stirring to obtain an anti-reflective self-cleaning coating for photovoltaic modules.

2. The method for preparing an anti-reflection self-cleaning coating for photovoltaic modules according to claim 1, characterized in that: In step S1, The mass ratio of the polyacrylic acid, ammonia water, anhydrous ethanol and tetraethyl orthosilicate is (1-2): (10-15): (150-180): (2-3); The mass fraction of the ammonia water is 15-20wt.%; The stirring time after adding ethyl orthosilicate is 6-8h.

3. The method for preparing an anti-reflection self-cleaning coating for photovoltaic modules according to claim 1, characterized in that: In step S1, The preparation method of the trifluoropropyl triethoxysilane solution is as follows: dissolving trifluoropropyl triethoxysilane in anhydrous ethanol to prepare a trifluoropropyl triethoxysilane solution, adding deionized water to the trifluoropropyl triethoxysilane solution and adjusting the pH, wherein the mass fraction of the trifluoropropyl triethoxysilane solution is 5-10wt.%; and the range of adjusting the pH is 4-5; The first temperature is 40-50°C; The mass ratio of the trifluoropropyltriethoxysilane solution after pH adjustment to deionized water is (10-15): (1-2); The reaction time of adding the pH-adjusted trifluoropropyltriethoxysilane solution is 2-3 hours.

4. The method for preparing an anti-reflective self-cleaning coating for photovoltaic modules according to claim 1, characterized in that: In step S2, The mass ratio of cyclopropylethyltrimethylsilyl acetal to 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether is (1-2):(70-80); The mass ratio of the benzoyl peroxide, 1H,1H-perfluorooctyl acrylate and another portion of 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether is (0.5-1.0):(20-30):(40-50); The second temperature is 65-75°C.

5. The method for preparing an anti-reflection self-cleaning coating for photovoltaic modules according to claim 1, characterized in that: In step S2, The reaction time after the reaction solution B is added to the reaction solution A is 6-8h; The third temperature is 80-90°C; The reaction time at the third temperature is 2-3h.

6. The method for preparing an anti-reflection self-cleaning coating for photovoltaic modules according to claim 1, characterized in that: In step S3, The mass ratio of the methyl methacrylate, octyl acrylate, hydroxyethyl acrylate, 2-hydroxyethyl acrylic acid, bis-3-methacryloxypropylated tetramethyldisiloxane, azobisisobutyronitrile, dodecanethiol, ethyl acetate, triethylamine and deionized water is (6-8): (6-8): (10-12): (1-3): (0.5-1): (0.2-0.5): (0.1-0.3): (40-50): (2-4): (20-30).

7. The method for preparing an anti-reflection self-cleaning coating for photovoltaic modules according to claim 1, characterized in that: In step S3, The fourth temperature is 90-100° C.; The reaction time at the fourth temperature is 1-2h.

8. The method for preparing an anti-reflection self-cleaning coating for photovoltaic modules according to claim 1, characterized in that: In step S3, The fifth temperature is 100-110° C.; The reaction time of the fifth temperature is 6-8h; The stirring time after adding triethylamine is 30-50min.

9. The method for preparing an anti-reflection self-cleaning coating for photovoltaic modules according to claim 1, characterized in that: In step S4, The cross-linking agent is methylated high-imino melamine; The mass fraction of the cross-linking agent solution is 20-30wt.%; The mass ratio of the modified SiO2 sol, the coating solution, the coating precursor solution, and the crosslinking agent solution is (30-50): (20-30): (30-50): (5-10); The stirring time after adding the cross-linking agent is 20-30 minutes.

10. An anti-reflective self-cleaning coating for photovoltaic modules obtained according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Transparent self-cleaning coating and preparation method of transparent self-cleaning coating for solar photovoltaic panel

    CN118994980A

  • Modified silica particles and dirt repellent polymer compositions comprising them

    US20100288963A1

  • Method for preparing nano-modified styrene-acrylic / siloxane graft copolymerized composite emulsion

    WO2024164754A1